Is natural bait type a stochastic process for size and condition of fishes in the recreational fishery of Ιzmir Bay? - AYDIN, I. (Mediterranean Marine Science, 2011)
Determining bait type might be one of the most important factors that influence the amount and size of the fish catch in marine recreational fishery. To this end, the relationships between two types of natural bait and catch per unit effort (CPUE), yield per unit effort (YPUE), fish size and condition (K=W/TL3) were evaluated in recreational fishery İzmir Bay (Middle Eastern Aegean Sea, Turkey). The most abundant angling species in Turkish coasts; annular sea bream (Diplodus annularis), blotched picarel (Spicara flexuosa), two banded sea bream (Diplodus vulgaris) and bogue (Boops boops) were collected by anglers between September 2006 – February 2007 with using baits; onyx (Solen vagina), and sardine (Sardina pilchardus). The average CPUE and YPUE of hooks baited with onyx were significantly higher than the bait sardine. Eventhough the averages of specimens caught with bait sardine were bigger than onyx except for bogue but, total length-frequency distributions were revealed some differences only for annular sea bream and blotched picarel between two baits. High conditioned individuals of bogue were caught with bait sardine and the rest of the other species with onyx.